The use of civilian-type GPS receivers by the military and their vulnerability to jamming - Andries Van Niekerk; Ludwig Combrinck (South African Journal of Science, 2012)
We considered the impact of external influences on a GPS receiver and how these influences affect the capabilities of civilian-type GPS receivers. A standard commercial radio frequency signal generator and passive GPS antenna were used to test the sensitivity of GPS to intentional jamming; the possible effects of the terrain on the propagation of the jamming signal were also tested. It was found that the high sensitivity of GPS receivers and the low strength level of GPS satellite signals combine to make GPS receivers very vulnerable to intentional jamming or unintentional radio frequency interference. Terrain undulation was used to shield GPS antennas from the direct line-of-sight of the jamming antenna and this indicated that terrain characteristics can be used to mitigate the effects of jamming. These results illuminate the vulnerability of civilian-type GPS receivers to the possibility and the ease of disablement and establish the foundation for future work.